Sulfur trioxide formation/emissions in coal‐fired air‐ and oxy‐fuel combustion processes: a review - Sarbassov, Yerbol; Duan, Lunbo; Manovic, Vasilije; Anthony, Edward J. (Wiley, 2018)
In oxy‐fuel combustion, fuel is burned using oxygen together with recycled flue gas, which is needed to control the combustion temperature. This leads to higher concentrations of sulfur dioxide and sulfur trioxide in the recycled gas, which can result in the formation of sulfuric acid and enhanced corrosion. Current experimental data on SO3 formation, reaction mechanisms, and mathematical modelling have indicated significant differences in SO3 formation between air‐ and oxy‐fuel combustion for both the wet and dry flue gas recycle options. This paper provides an extensive review of sulfur trioxide formation in air‐ and oxy‐fuel combustion environments, with an emphasis on coal‐fired systems. The first part summarizes recent findings on oxy‐fuel combustion experiments, as they affect sulfur trioxide formation. In the second part, the review focuses on sulfur trioxide formation mechanisms, and the influence of catalysis on sulfur trioxide formation. Finally, the current methods for measuring sulfur trioxide concentration are also reviewed along with the major difficulties associated with those measurements using data available from both bench‐ and pilot‐scale units.
Keywords: Oxy-fuel combustion; sulfur dioxide; sulfur trioxide formation; catalysis